Pengaruh Pelaksanaan Supervisi Akademik terhadap Peningkatan Kompetensi Pedagogik Guru di SDN Margorejo VI/524 dan SDN Baratajaya - Rohmi, Fauriza; Nafiah, Nafiah (Universitas Nahdatul Ulama Surabaya, 2019)
The Effect of Academic Supervision to Improve Pedagogy Competency of Teacher of Margorejo VI/524 Elementary School and Baratajaya Elementary School of Surabaya. The headmaster is fully responsible for organizing education with teachers as class teachers. Teachers are required to master four competencies, one of which is pedagogical competence. However, not all teachers master these competencies, so it is the responsibility of the headmaster to conduct academic supervision. The activity is carried out in the form of class meetings / visits. Therefore, teachers can improve their pedagogical competencies. Researchers are interested in conducting research that aims to analyze the existence of academic supervision in SDN Margorejo VI / 524 and SDN Baratajaya Surabaya. Both schools are located in Surabaya. In addition, the study was conducted also, with the aim to examine the effect of the implementation of academic supervision on the pedagogical competence of teachers by using descriptive quantitative research methods and Spearman rank correlation with ordinal scale data. The population of the two schools is 102 respondents. Sample is 81 respondents with an error level of 0.05. Observation with a questionnaire that has proven as valid and reliable. The analysis by using SPSS 21. The study used two data analysis techniques, namely descriptive analysis and Spearman rank correlation analysis. The results showed that the two schools had carried out academic supervision activities to improve teacher pedagogical competence. The results obtained were 0.608 which means that the category is very good and good and classified as moderate correlation, with a significant correlation value of 0,000 <0.05. So the hypothesis in this study that H1 is accepted and H0 is rejected.